Environmental legislation and the impact of lobbying activities - Elga Bartsch; Ingo P. Thomas; Michael Rauscher (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
The paper is concerned with effects of lobbying activities by political pressure groups that wish to affect environmental legislation. Two interest groups are considered, environmentalists on the one hand and a polluters' lobby on the other. These two groups can influence the environmental policy in two ways. First, they support those political parties that promise to implement their favoured kind of environmental regulation. This support has an impact on election probabilities and, therefore, on the environmental policy measures implemented by the new government. The second way of influencing political decisions is to exert pressure on an existing government. These two approaches are used in the paper to address the questions of how environmental quality is affected by lobbying activities and how large the resource waste due to lobbying is.
Keywords: 330; Umweltpolitik; Interessenpolitik; Theorie